Application of poultry manure as an energy resource by its gasification in a prototype rotary counterflow gasifier. (September 2021) - Sitka, Andrzej; Szulc, Piotr; Smykowski, Daniel; Jodkowski, Wiesław
Abstract: The paper presents the study focused on the application of poultry manure as an energy resource. Such solution is expected to bring limitation of fossil fuels exploitation, reduction of poultry farming costs, as well as sustainable waste to energy conversion. The study was performed by the use of a prototype gasification installation. The study involved analysis of the outlet gas composition, calorific value and flue gas emission. Measured heat of combustion of dry poultry manure is comparable to wood or straw. It contains relatively large amount of ash (9.11%), volatile components (78.4%) and low amount of sulphur. The chemical composition of obtained ash, shows low contribution of components elevating the melting temperature and high contribution of components decreasing the melting temperature, which indicates slagging tendency. The calorific value of the process gas, ranges from 6.47 MJ/m 3 to 9.47 MJ/m 3 . Measured emission values match the applicable standards, except dust content. Performed studies indicated that poultry manure is a valuable energy resource, which allows to reduce the use of fossil fuels for the needs of poultry farming. Obtained results are essential for the design and operation of gasification installation in order to avoid operation problems associated with slagging of the gasification chamber. Highlights: Poultry manure is a valuable energy resource, however has some drawbacks, e.g. ash. Gasification of poultry manure allows to eliminate drawbacks of its direct use. Calorific value of the process gas ranges from 6.47 MJ/m 3 to 9.47 MJ/m 3 . Emission values match the applicable standards, except dust content. Poultry manure allows to replace fossil fuels with biofuels in poultry farming.